Mapping and Profiling Legume Seed Value Chain Actors in Morocco: Chickpea and Lentil - Bishaw, Zewdie; Imtiaz, Muhammad; Yigezu, Yigezu; Lammari, Abdelali; Rredani, Latifa; Boughlala, Mohamed (International Center for Agricultural Research in the Dry Areas, 2024)
In Morocco, food legumes occupied as large areas as 600 thousand ha in the early 1970s. Thereafter, however, the area under food legumes fluctuated with a general downward trend. For the period 2001-2010, the annual average was 427 thousand ha per year which decreased to 404 thousand ha between 2011 and 2022. In 2024, the area allocated to food legumes is about 200 thousand ha. The decline in food legumes area is due not only to climate variability (periodic droughts) but mainly to other factors such as diseases (including Orobanche and Ascochyta Blight), increased mono-cropping of cereals and other crops, and lack of appropriate technologies (such as lack of high yielding, water efficient, and short duration varieties which are also amenable to mechanization). Moreover, the market for food legumes still suffers from poor organization because it remains controlled by several intermediaries that are exploiting their power to extract more than their fair share of the price without making comparable value addition thereby reducing the price received by food legume producers. In these conditions, more efforts are needed to improve food legume production and rehabilitation. As part of the solution to revitalize food legumes, this study aims to investigate the systemic challenges of the seed system and identify the constraints and opportunities of the main stakeholders. Due to time and resource constraints, only lentils and chickpeas were targeted. According to the results of interviews and surveys, legumes-certified seed production is far from being a priority for the Ministry of Agriculture, Fisheries, Rural Development, Water and Forests (MARDWF). However, it is important to note that many actors are involved in the seed sector and the most important ones are AMMS, INRA, FNIS, ONSSA, ONCA, and COMADER. The private sector is involved in the seed sector but not in food legumes. According to the Moroccan Seed Growers Association (AMMS), the Department of Agriculture will launch a new initiative in the 2024-2025 cropping season by targeting seed multipliers operating within the aggregation system and including them under contracts for certified seed multiplication. The constraints of the legume sector do not pertain to only the production of certified seed, but also to the lack of appropriate varieties, limited number of herbicides, lack of sufficient incentives, high demand for labor, and mechanization.